ANALISIS MEKANISME TRANSMISI KEBIJAKAN MONETER TERHADAP INFLASI - Mita Ratna Sari; Yeniwati Yeniwati (Universitas Negeri Padang, 2019)
This study aims to determine the effect of the BI Rate through the transmission of interest rates on Bank Indonesia Certificates (SBI), interest rates on the Interbank Money Market (PUAB), loan interest rates and deposit rates on inflation. The type of research used is associative descriptive research. The type of data in this study is secondary data and time series in the form of quarterly data from 2001 to 2016. Analysis of the data used is descriptive analysis and inductive analysis. The method used is Moderated Regression Analysis (MRA), in the inductive analysis there are tests, namely: Moderated Regression Analysis (MRA), classic assumption test and t test. These results show that: (1) the BI Rate has a significant effect through the transmission of SBI interest rates to inflation (2) the BI Rate has a significant effect through the transmission of interbank rates to inflation (3) the BI Rate has a significant effect through transmission of lending rates to inflation (4) The BI Rate has no significant effect through the transmission of deposit rates to inflation.